System Parameters Sensitivity Analysis of Ocean Thermal Energy Conversion - . Rasgianti; Ristiyanto Adiputra; Ariyana D. Nugraha; Ruly B. Sitanggang; Wahyu W. Pandoe; . Aprijanto; Takeshi Yasunaga; Muhammad A. Santosa (Ital Publication, 2024)
Ocean Thermal Energy Conversion (OTEC) is a technology to harvest the solar energy stored in the ocean by utilizing the temperature difference between warm surface and cold deep seawater. Considering that the OTEC system works in a low-temperature range, the present paper assessed the technical resources comprehensively by acquiring in-situ thermocline data and conducting a sensitivity analysis of the system parameters. The in-situ temperature profile data were measured in the waters of North Bali, Indonesia. The temperature gradient data based on field measurements were then compared with the HYCOM consortium model. The data were then used as input in the OTEC power and efficiency estimation through a single-stage ranking cycle. The analysis was conducted by varying the type of working fluid, the performance of the heat exchanger, and the location to investigate how the system parameters influenced the power produced. Using an unusual combination of parameters made it difficult to analyze the resulting data multiple times. However, with reference-based analysis and the formulation of calculations, the sensitivity of each parameter could be assessed at both locations. As a result, the ammonia working fluid provided the highest net power output of the system but had the lowest efficiency of all working fluids. The heat exchanger performance in terms of net power and efficiency cannot be separated from the seawater mass flow requirement. This referred to the results where the heat exchanger with a temperature difference of 3°C before and after the seawater passed through the heat exchanger and produced the highest net power and efficiency. Additionally, the net power output reached its convergence level at a water depth of 400m for the Bungkulan site and 450m for Celukan Bawang, which was proportional to the thermocline tendency. Doi: 10.28991/ESJ-2024-08-02-04 Full Text: PDF